Dual Sounding Rocket and C/NOFS Satellite Observations of DC Electric Fields and Plasma Density in the Equatorial E‐ and F‐Region Ionosphere at Sunset. Issue 5 (29th April 2022) - Pfaff, R.; Kudeki, E.; Freudenreich, H.; Rowland, D.; Larsen, M.; Klenzing, J.
Abstract: E × B plasma drifts and plasma number density were measured on two NASA rockets launched simultaneously at sunset from Kwajalein Atoll with apogees of 182 and 331 km, with similar, coincident measurements gathered on the Communications/Navigation Outage Forecasting System (C/NOFS) satellite at 390 km. The combined measurements portray a highly dynamic ionosphere in a narrow range of local time and altitude, providing evidence of vortex‐like motions. Although the vertical plasma drift was upwards, its magnitude was not constant, increasing between ∼150 and 250 km altitude where the plasma density was reduced. The zonal plasma drifts displayed a shear with altitude, changing from eastward to westward flow below 270 km, coincident with the larger upward drifts and consistent with the maintenance of the vortex flow. The plasma density on the western flank was highly structured compared to the eastern flank, despite the fact that the western region corresponded to slightly earlier local times. These observations illustrate that the low latitude ionosphere at sunset must be considered as an ensemble of interconnected flows encompassing an evolving "theater, " as opposed to a background that simply unfolds linearly with respect to local time. The observations also underscore how satellites at high altitudes do not capture the highly dynamic ionosphere and thermosphere at the lower altitudes which are critical for understanding the electrodynamics system. Such motions set the stage for large scale plasma instabilities to form later in the evening, as observed by radars at Kwajalein and subsequent passes of the C/NOFS satellite. Plain Language Summary: Earth's upper atmosphere and ionosphere undergo significant variations between day and night. At sunset, the directions of the ionosphere motions, represented by electric fields, and the upper atmosphere winds, are known to reverse direction at low latitudes. NASA launched two rockets simultaneously with different apogees precisely at sunset from the low latitude launch pad at Kwajalein Atoll to examine how the plasma and neutral dynamics behave during this transitional period. The results reveal a surprisingly complex, though organized, system of flows that change significantly within a very narrow local time period, creating a vortex pattern with respect to altitude and local time. Furthermore, how the low latitude ionosphere evolves within this sunset "theater" is key to understanding how the subsequent nighttime ionosphere might eventually become unstable, creating irregularities responsible for scintillations that disrupt communication and navigation radiowaves. Key Points: Vertical profiles gathered on rockets reveal highly complex, though organized, electrodynamics in the low latitude ionosphere at sunset Zonal plasma drifts display shears with altitude, suggesting a vortex pattern, which may establish unstable ionospheric conditions Electric field and plasma density measurements on a pair of sounding rockets provide unique measurements in the sunset ionosphere